PROFESSIONAL ACTIVITY OF STUDENT'S YOUTH: SOCIAL FACTORS OF DETERMINATION - M. A. Kovziridze (Модернизация, инновация, развитие, 2016)
Sociological studying of social orientations of youth allows to see the importance and width of researches, having presented them as a public problem for which decision the account of the economic, socially-psychological and demographic parties is necessary. In article were investigatedformation of standards of market behaviour of student’s youth that serves as a necessary condition of fastening in a modern society of new norms and values of labour and property relations, adaptation to market institutes.